청주시 일부 중학생들의 치과공포도와 치과공포 요인 - 심연수(Youn-Soo Shim); 김아현(Ah-Hyeon Kim); 안소연(So-Youn An) (한국콘텐츠학회 논문지, 13(9), 2013)
This study aims to examine the level of fear and the influential factors affecting their dental fear and to utilize the result as the basic materials in the dental management. The subjects were the students from a middle school located in Cheongju-City. The school was selected by convenient sampling and self-answered questionnaire was filled in by the students for a week from December 19th 2011. The survey result showed that 77 male students and 169 female students(total 246 students) answered 'yes' to the question 'Have you ever felt fear when you visited a dentist?' among 475 students who had visited a dentist in the past. The distribution of responses in each category of fear was examined by frequency analysis. The study results showed significant difference in the item of 'causing irritation during the dental treatments' between male students and female students (p<0.05). Converting the level of fear into scores after marking the answers, the score of male students was 52.0 points and the score of female students was 58.53 showing the score of female students was significantly higher in statistics. Moreover, the fear score of female students for the category 'causing irritation during the dental treatments' was also significantly higher in statistics(p<0.05). Therefore, these results should be reflected to the dental care environments in order for the adolescent to reduce the dental anxiety and fear. 본 연구에서는 중학생을 대상으로 치과치료에 대한 치과공포도와 요인을 조사함으로써 치과의료 관리측면에서 활용하는 기초 자료를 연구하고자 수행되었다. 청주시 소재 1개 중학교를 편의 추출하여 2011년 12월 19일부터 일주일 동안 자기기입식 설문조사를 실시하였고, 설문 결과 치과 방문 경험이 있는 475명 중, '치과 방문 시 공포를 느낀 적이 있습니까?'라는 문항에 '예'라고 대답한 남학생 77명, 여학생 169명, 총 246명의 자료를 이용하였다. 각 공포 원인의 범주별 답변의 분포를 알아보기 위해 빈도분석을 실시하였으며, 분석 방법은 남녀별 응답의 차이를 검정하기 위해 교차분석과 범주별 공포점수의 비교를 위하여 독립표본 T 검정을 실시하였다. 연구 결과 '치과 진료 시 자극 유발'의 범주의 문항에서 남녀 간의 차이가 존재하였다(p<0.05). 각 문항의 답을 점수화 하여 공포도를 점수로 환산한 결과에서 남학생은 평균 52.0점, 여학생은 평균 58.53점으로 여학생의 점수가 남학생에 비해 통계적으로 유의하게 높은 것으로 나타났다. 그리고 범주별 공포도 점수는 '치과 진료 시 자극 유발'의 범주에서 여학생이 남학생보다 통계적으로 높은 공포도를 보이는 것으로 나타났다(p<0.05). 따라서 이러한 결과를 치과 진료 환경에 반영하여 청소년들의 치과 공포를 줄일 수 있도록 하는 배려가 필요하다.